Taking the reins: A grounded theory study of women's experiences of negotiating water immersion for labour and birth after a previous caesarean section. Issue 2 (March 2023) - Townsend, B.; Fenwick, J.; McInnes, R.; Sidebotham, M.
Abstract: Background: Women seeking a vaginal birth after a caesarean section (VBAC) frequently want to keep their subsequent labour and birth free from intervention. Water immersion (WI) during labour is potentially an effective tool for women having a VBAC for its natural pain-relieving properties. However, negotiating access to WI can be difficult, especially in the context of VBAC. Aim: To explore women's experiences of negotiating WI for labour and birth in the context of VBAC. Methodology: This Grounded Theory study followed Strauss and Corbin's framework and analytic process. Twenty-five women planning or using WI for their VBAC labour or birth were recruited from two midwifery practices and a social media group across Australia. Participants were interviewed during pregnancy and/or postnatally. Findings: 'Taking the reins', the core category explaining the women's experiences of assuming authority over their birth, comprised five categories: 'Robbed of my previous birth experience'; 'My eyes were opened'; 'Water is my tool for a successful VBAC'; 'Actioning my choices and rights for WI', and 'Empowered to take back control'. 'Wanting natural and normal' was the driving force behind women's desire to birth vaginally. Two mediating factors: Having someone in your corner and Rules for birth facilitated or hindered their birth choices, respectively. Conclusion: The women became active participants in their healthcare by seeking information and options to keep their birth experience natural and normal. Support from other women and advocacy in the form of continuity of midwifery care was crucial in successfully negotiating WI for their VBAC when navigating the complex health system.